Implications of Tahura Pocut Meurah Intan Deforestation on Plant Diversity for Bucerotidae Bird Feed in Aceh Province - Kamal, Samsul; Djufri, Djufri; Sarong, Muhammad Ali; Rusdi, Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Abstract: This study investigates the ecological impact of forest destruction within the Pocut Meurah Intan Grand Forest Park, specifically focusing on its implications for food availability for the avian family Bucerotidae. The research aims to examine the practices contributing to forest destruction within the Tahura ecosystem, analyze the consequential effects of this destruction on the diversity of food sources available to Bucerotidae species, and propose potential solutions to mitigate the identified challenges to Bucerotidae sustenance. Employing an exploratory survey methodology, the research utilizes direct observation techniques to gather data at the study site. Qualitative descriptive analysis is employed to interpret the collected data and draw meaningful conclusions. The distribution of deforestation locations was analyzed using ArcGIS software. The distribution of forest damage is displayed in maps, pictures, and tables. The study results showed that forest damage in the Tahura Pocut Meurah Intan area resulted in forest conversion into plantations, illegal logging, and forest burning for business purposes. There are nine species of bird feed plants in the Bucerotidae family found in Tahura Pocut Meurah Intan. The implications of forest destruction include decreasing the number of bird feed plants of the Bucerotidae family. The species were Ara Hutan (Ficus fistulosa Reinw ex Blume), Beringin (Ficus benjamina L), Empanai (Ficus altassima L), Ndalai (Ficus ampelas Burm.F), Medang (Litsea glutinosa (Lour.) C.B. Robinson), Rambai (Baccaurea bracteata Müll.Arg), Walen (Ficus virens W.A.T.). The remaining nine species are dominated by the Moracea family (77%); in addition, there are also plant species from the Euphorbiaceae (14%) and Phyllanthaceae (9%). Ensuring the sustained availability of food plant resources for the Bucerotidae family necessitates a multi-pronged approach; Habitat restoration through the reclamation of degraded forest areas is crucial; Enhancing community awareness regarding the ecological and economic importance of forest ecosystems is essential for promoting sustainable practices; Bolstering surveillance and enforcement within the Tahura Pocut Meurah Intan forest area, through increased monitoring and the active involvement of Forest Police, law enforcement agencies, local communities, and environmental NGOs, is vital to deter illegal activities and protect existing resources; And consistent application of existing environmental regulations is paramount to ensuring the long-term preservation of the Bucerotidae food plant supply.Abstrak: Penelitian ini menyelidiki dampak ekologis kerusakan hutan di Taman Hutan Raya Pocut Meurah Intan, khususnya berfokus pada implikasinya terhadap ketersediaan makanan bagi famili burung Bucerotidae. Penelitian bertujuan untuk mengetahui kerusakan hutan ekosistem Tahura Pocut Meurah Intan, implikasi kerusakan terhadap keanekaragaman pakan burung Bucerotidae, dan solusi terhadap ketersediaan pakan burung Bucerotidae. Metode yang digunakan adalah survei eksploratif dengan teknik observasi langsung ke lokasi objek penelitian. Analisis data tentang deforetasi dianalisis dengan software ArcGis. Penyajiannya dalam bentuk peta, gambar dan tabel. Hasil penelitian menunjukkan bahwa kerusakan hutan di kawasan Tahura Pocut Meurah Intan berupa konversi hutan menjadi perkebunan, penebangan liar (illegal logging), dan pembakaran hutan untuk tempat usaha; spesies pakan burung Bucerotidae yang terdapat di Tahura Pocut Meurah Intan (TPMI) sebanyak 9 spesies, dan implikasi kerusakan hutan TPMI berdampak terhadap menurunnya jumlah spesies pakan burung Bucerotidae. Spesies yang dimaksud adalah Ara Hutan (Ficus fistulosa Reinw ex Blume), Beringin (Ficus benjamina L), Empanai (Ficus altassima L), Ndalai (Ficus ampelas Burm.F), Medang (Litsea glutinosa (Lour.) C.B. Robinson), Rambai (Baccaurea bracteata Müll.Arg), Walen (Ficus virens W.A.T.). Familia yang mendominasi adalah Moraceae (77%), selanjutnya Euphorbiacea (14%), dan Phyllanthaceae (9%). Upaya yang perlu dilakukan untuk menjaga kelestarian tumbuhan pakan burung Bucerotidae adalah; Melakukan reklamasi hutan yang mengalami kerusakan; Penguatan pemahaman masyarakat tentang fungsi hutan; Penguatan dan peningkatan pengawasan kawasan hutan; Penegakan hukum di kawasan hutan Tahura Pocut Meurah Intan dengan melibatkan Polisi Hutan (Polhut), kepolisian, masyarakat, dan LSM pemerhati lingkungan; serta penerapan peraturan lingkungan yang ada secara konsisten sangat penting untuk memastikan kelestarian pasokan tanaman pangan Bucerotidae dalam jangka panjang.